How Do Binus University Undergraduate Students Value English in the General, Academic, and ELT Context? - Almodad B. Asmani (Lingua Cultura, 2010)
Article  explored the issues of the reasons and ways Indonesian undergraduate students taking English subjects at Binus University valued English, particularly in relation to its roles and influences as the dominant language and as the world’s lingua franca, and how these could give impacts on the ELT (English Language Teaching) purposes at Binus University. The study used the quantitative approach to find out the pattern of the ways they valued English in the general, academic and ELT contexts. The analysis of the quantitative results showed that there was a tendency that non-computer students value English relatively higher than computer students in terms of linguistically imperialistic ideas and macroacquisition views, while English itself tended to be respected by all students for both reasons of material/non-material benefits as well as international influences. In summary, teacher resources, teaching techniques, curriculum design, material content and assessment format should put these findings into consideration so as to make the best teaching methodology for ELT practices at Binus University.